1976
DOI: 10.1017/s0003356100035431
|View full text |Cite
|
Sign up to set email alerts
|

Studies in sow reproduction 4. The effect of level of feeding in lactation and during the interval from weaning to remating on the subsequent reproductive performance of the early-weaned sow

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0003356100035431How to cite this article: M. A. Varley and D. J. A. Cole (1976). Studies in sow reproduction 4. The effect of level of feeding in lactation and during the interval from weaning to remating on the subsequent reproductive performance of the early-weaned sow. SUMMARY Seventy-five enzootic pneumonia-free female pigs (sows) were allocated at random to one of five treatment groups. Four of these groups were weaned following a 10-day lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

1976
1976
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 10 publications
3
14
0
1
Order By: Relevance
“…Hughes and Calder (1979) and Reese et al (1982a,b) demonstrated that increasing energy intake during lactation can reduce the number of days to rebreeding. However, Varley and Cole (1976)reported no effect of feeding level during lactation on the number of days to return to estrus following weaning, even though sow weight loss was affected by feeding level during lactation. Since no differences were observed in sow weight loss in this study, other factors must account for the difference in rebreeding interval.…”
Section: Resultsmentioning
confidence: 91%
“…Hughes and Calder (1979) and Reese et al (1982a,b) demonstrated that increasing energy intake during lactation can reduce the number of days to rebreeding. However, Varley and Cole (1976)reported no effect of feeding level during lactation on the number of days to return to estrus following weaning, even though sow weight loss was affected by feeding level during lactation. Since no differences were observed in sow weight loss in this study, other factors must account for the difference in rebreeding interval.…”
Section: Resultsmentioning
confidence: 91%
“…Farrowing rate (i.e., number of sows farrowed/number mated) was not significantly affected by energy intake during Lac 1. Although farrowing rate was not reported, Lidvall and Griffin (1962), Elsley et al (1969), Hitchcock et al (1971) and Varley and Cole (1976) reported that lactation feeding level had no influence on conception rate of sows. Similarly, energy intake during Lac 1 had no significant influence on the total number of fully developed pigs born or born alive; however, sows fed Lo farrowed lighter weight (P<.10) pigs than those fed Hi.…”
Section: Resultsmentioning
confidence: 99%
“…Elsley et al (1968) and Adam and Shearer (1975) reported that energy intake during the previous lactation had no influence on the number of pigs born and average pig birth weight. Feed intake during lactation also had no influence on litter size at birth Hitchcock et al, 1971;Varley and Cole, 1976) and birth weight O'Grady et al, 1973;Varley and Cole, 1976). O'Grady et al (1973) reported that the number of pigs born alive decreased as energy intake increased during the previous lactation.…”
Section: Resultsmentioning
confidence: 99%
“…Sows weaned from their litters following lactation lengths of less than 3 weeks are characterized by an increased interval from weaning to the next oestrus and by a reduction in litter size at the next farrowing (Smidt, Scheven and Steinbach, 1965;Aumaitre and Rettagliati, 1972;te Brake, 1972;Cole, Varley and Hughes, 1975;Varley and Cole, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some evidence that ovulation rate is implicated in this, Varley and Cole (1976) have suggested that embryo mortality may be of greater importance. The work reported here was undertaken to determine the relative importance of these two factors.…”
Section: Introductionmentioning
confidence: 99%